ANALISIS YURIDIS KRIMINOLOGIS TENTANG KEKERASAN DALAM RUMAH TANGGA YANG DILAKUKAN OLEH ISTRI TERHADAP SUAMI - Zulkarnain Zulkarnain (Widya Yuridika, 2018)
Household violence is a serious phenomenon that should be catered for due to its seriousness; it is not only done by the husband, who its mostly the doer of the action, but also by the wife. As a result, it is urgent to put the laws forbidingthe practice of such a householdviolence into effect. The laws control the protection of the victims in a household. Paradoxically, the enforcement, however, may trigger new modes of household violence, namely the violence done by the wife. The modes of violence are various in type. In criminology studies, it is shown that the violence by the wife is caused by many causes. Further analyses (using a causalteit theory in criminal law) suggest that the violence by the wife is marely a negative reaction against the violence by the husband. On the basis of such of phenomenon, the law enforcement underscores socio-criminological aspects in order to realize a criminal individualization-based justice. Making a wife into a criminal case as a form of a repressive action of the violence just hide the real forms of household violence mostly done by the husband. Kata kunci: Kekerasan dalam rumah tangga, kekerasan istri, penegakan hukum